Pants on Fyre: parasitic masculinity and the Fyre festival documentaries. Issue 1 (2nd January 2023) - Hoerl, Kristen; Kelly, Casey Ryan
ABSTRACT: The documentaries Fyre Fraud and FYRE: The Greatest Party that Never Happened recount the fraudulent and imprudent decision-making process that led up to the ill-fated Fyre Fest . These documentaries represent the music festival's failure through depictions of white masculinity that seek parasitic attachment and proximity to the hegemonic ideal of masculine authority in the neoliberal marketplace. We argue that these movies map the operations of an imitative form of white masculine subjectivity that thrives in precarity, even as they recuperate the status of late-stage neoliberalism by symbolically removing parasitic masculinity from the neoliberal social order that it feeds on.